(untitled) (Research, Society and Development, 2020)
The aim of this study was to describe the relationship between the family and the social networks of care for children with special health care needs. This is a qualitative research conducted with ten families of these children. Data collection was conducted between January and February 2012, we used the triangulation technique for data collection: desk research, semi-structured interview, building genogram and eco-map. For data analysis we used the thematic content analysis. The results show that social networks are limited and specific. The difficulties in access to health services and education. We conclude that the difficulties experienced by the families of these are related to the completeness and accessibility to services and health actions. It is recommended actions centered on the child and his family, the promotion and coordination of social networks, for the reorganization of family dynamics.